Canada: National-building in a federal welfare state - Keith G. Banting (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2004)
In Canada, three distinct models of federalism govern different social programmes: classical federalism, with programmes run exclusively by one level of government; shared costs federalism, with the federal government financially supporting provincial programmes; and joint-decision federalism, where formal approval by both levels of government is mandatory before any action can take place. Each of these models creates different decision rules, altering the mix of governments and ideologies at the bargaining table, redistributing power among those who have a seat at the table, and requiring different levels of consensus for action. The result has been three separate kinds of interactions between institutions and policy during the postwar era of welfare state expansion. As in the era of expansion, the new politics of social policy in the 'silver age' had to flow through the three distinctive institutional filters created by federal institutions, helping to explain the uneven impact of retrenchment in Canada. Exclusively federal programmes were unprotected by intergovernmental relations and fully exposed to shifts in national politics, with dramatic cuts especially in unemployment benefits. In contrast, joint-decision federalism helped protect contributory pensions from radical restructuring; while sharedcost federalism made it possible to preserve the basic model of the health care system, at least in respect of hospital, physician and diagnostic services, if not always in respect of the generosity of funding. – – Drei unterschiedliche Föderalismusmodelle charakterisieren Kanadas Sozialpolitik: Politikverflechtung, klassischer (dualer) Föderalismus und `shared costs federalism'. Jedes dieser Modelle generiert unterschiedliche Entscheidungsregeln, Akteurs- und Machtkonstellationen sowie Konsensschwellen für politisches Handeln und hat folglich sowohl die Expansion des kanadischen Wohlfahrtsstaates als auch dessen Rückbau unterschiedlich beeinflusst. Während die Politikverflechtung auf dem Gebiet der beitragsfinanzierten Renten sowohl den Programmausbau als auch den –rückbau gebremst hat, wurden die ausschließlich vom Bund regulierten Programme sowohl in der Expansionsals auch in der Konsolidierungsphase maßgeblich von den politischen Kräfteverhältnissen auf der nationalen Ebene bestimmt. Der in der Gesundheitspolitik praktizierte shared costs federalism bot in der Expansionsphase Raum für sozialpolitische Innovationen auf der Provinzebene, die einem sozialdemokratischen Gesundheitssystem Vorschub leisteten. Dieses Modell blieb in seinen Grundzügen in der Rückbauphase zwar bestehen, gleichzeitig zog sich Ottawa jedoch aus der Finanzierung des Gesundheitswesens zurück.
Keywords: 300